2020
DOI: 10.1109/access.2019.2962235
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Satellite Telemetry Data Classification Based on Self-Learning

Abstract: Since great redundancy of telemetry data of spacecraft, telemetry data compression is a good solution for the limited bandwidth and contact wireless links. It is important to obtain accurate data characteristic firstly. State-of-the-art machine learning methods work well on data mining and pattern recognition under conditions of the given test data set, which could be used as the available tools for post-event data processing and analysis, such as trend forecasting and outlier detection, but they have not prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…To classify satellite image datasets and samples, a variety of models, including CNNs, SVMs, DTs, DBNs, and ensemble models, are employed. Every model has advantages and disadvantages, and the selection of a model depends on the needs of the specific application [30,31,32]. Recent research has demonstrated that deep learning models such as CNNs and DBNs outperform more conventional machine learning models such as SVMs and DTs in satellite image classification tasks [33,34,35].…”
Section: Literature Reviewmentioning
confidence: 99%
“…To classify satellite image datasets and samples, a variety of models, including CNNs, SVMs, DTs, DBNs, and ensemble models, are employed. Every model has advantages and disadvantages, and the selection of a model depends on the needs of the specific application [30,31,32]. Recent research has demonstrated that deep learning models such as CNNs and DBNs outperform more conventional machine learning models such as SVMs and DTs in satellite image classification tasks [33,34,35].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In their study of the use of AI for fault diagnosis in general and for space utilization, Sun et al [125] argued that the most promising direction is the use of DL; suggested its usage for fault diagnosis for space utilization in China. By comparing different ML algorithms using telemetry data from the Egyptsat-1 satellite, Ibrahim et al [126] demonstrated the high prediction accuracy of LSTM, ARIMA, and RNN models. They suggested simple linear regression for forecasting critical satellite features for short-lifetime satellites (i.e., 3-5 years) and NNs for long-lifetime satellites (15-20 years).…”
Section: Ai-based Solutionsmentioning
confidence: 99%
“…In recent years, AI and ML techniques have been largely considered in solving challenges related to satellite communications such as beam hopping [158], channel modeling [159], and telemetry mining [160]. Employing FL in satellite-aerialterrestrial networks is still in its infancy; thus, there is plenty of room to explore the potential of FL in such networks.…”
Section: ) Cell-free Massive Mimo (Cfmmimo)mentioning
confidence: 99%